2020
DOI: 10.4103/jfmpc.jfmpc_84_20
|View full text |Cite
|
Sign up to set email alerts
|

Cauterization tonsillectomy as compared to traditional tonsillectomy technique

Abstract: Background: Tonsillectomy is one of the most frequently applied and oldest surgical procedures in otorhinolaryngology. Various surgical techniques are used to perform this operation including traditional and cauterization techniques. Objectives: To assess morbidity and efficacy and compare objectively the techniques in tonsillectomy, i.e., traditional technique and cauterization technique. This study compares the traditional and cauterization tonsillectomy techniques in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…We found, time of operation was significantly higher in dissection method group than cauterization method group, average operative time was 25-30 minutes in dissection method and 10-15 minutes in electrocautery (p=0.001). Al�Shehri et al reported that the median time spent for the traditional tonsillectomy was 21.5 min (range, 18-25 min) compared to cauterization method that has a median time of 9 min (range, 5-13 min) 4 . The difference between mean operative times of the two methods was statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found, time of operation was significantly higher in dissection method group than cauterization method group, average operative time was 25-30 minutes in dissection method and 10-15 minutes in electrocautery (p=0.001). Al�Shehri et al reported that the median time spent for the traditional tonsillectomy was 21.5 min (range, 18-25 min) compared to cauterization method that has a median time of 9 min (range, 5-13 min) 4 . The difference between mean operative times of the two methods was statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…With the increased popularity of day case surgery, fast procedures with short recovery are preferred. If at all feasible, the procedure should be painless, allowing for a quicker return to normal food and everyday activities 4 .…”
Section: Table Ii: Time Of Operation Of the Study Patients (N=400) Op...mentioning
confidence: 99%
“…Post-tonsillectomy pain is thought to arise from pharyngeal mucosal inflammation, which produces local nerve irritation and pharyngeal muscle spasm. 6 It is possible that enhanced nociception is associated with unique changes in patients' metabolic profile. This hypothesis has not been previously tested.…”
Section: Introductionmentioning
confidence: 99%
“…Tonsillectomy is one of the oldest and the most common surgical procedure constituting 20% of all otorhinolaryngology surgeries done worldwide. 1,2 Although tonsillectomy is a welltolerated surgery, it is still not devoid of complications. 3 Posttonsillectomy hemorrhage is the most frequently encountered complication after tonsillectomy, in addition to pain, dehydration, airway obstruction, vomiting and pulmonary edema.…”
Section: Introductionmentioning
confidence: 99%
“…7 This reason along with the low cost and ease of the procedure conventional dissection and electrocauterization tonsillectomy are still the two most commonly used techniques. 8,2 Nevertheless there is no consensus in optimal method of tonsillectomy. 9 Hence we chose to conduct a study comparing conventional dissection and bipolar electrocauterization tonsillectomy.…”
Section: Introductionmentioning
confidence: 99%